A Statistical Study of IRIS Observational Signatures of Nanoflares and Nonthermal Particles - Kyuhyoun Cho; Paola Testa; Bart De Pontieu; Vanessa Polito (The Astrophysical Journal, 2023)
Nanoflares are regarded as one of the major mechanisms of magnetic energy release and coronal heating in the solar outer atmosphere. We conduct a statistical study on the response of the chromosphere and transition region to nanoflares, as observed by the Interface Region Imaging Spectrograph (IRIS), by using an algorithm for the automatic detection of these events. The initial atmospheric response to these small heating events is observed, with IRIS, as transient brightening at the foot points of coronal loops heated to high temperatures (>4 MK). For four active regions, observed over 143 hr, we detected 1082 footpoint brightenings under the IRIS slit, and for those we extracted physical parameters from the IRIS Mg ii and Si iv spectra that are formed in the chromosphere and transition region, respectively. We investigate the distributions of the spectral parameters, and the relationships between the parameters, also comparing them with predictions from RADYN numerical simulations of nanoflare-heated loops. We find that these events, and the presence of nonthermal particles, tend to be more frequent in flare productive active regions, and where the hot 94 Å emission measured by the Atmospheric Imaging Assembly is higher. We find evidence for highly dynamic motions characterized by strong Si iv nonthermal velocities (not dependent on the heliocentric x -coordinate, i.e., on the angle between the magnetic field and the line of sight) and asymmetric Mg ii spectra. These findings provide tight new constraints on the properties of nanoflares and nonthermal particles in active regions, and their effects on the lower atmosphere.